Successful Treatment of a Recurrent Choroid Plexus Carcinoma with Surgery Followed by High-Dose Chemotherapy and Stem Cell Rescue. (1st August 2013) - Mosleh, Othman; Tabori, Uri; Bartels, Ute; Huang, Annie; Schechter, Tal; Bouffet, Eric
Abstract : Choroid plexus carcinoma (CPC) is a rare central nervous system malignant tumor with a dismal prognosis, especially in the case of incomplete resection or recurrence. The authors report long-term survival of a 1-year-old patient with recurrent CPC and Li-Fraumeni syndrome with surgical resection and high-dose chemotherapy (HDC) consisting of single cycle of Busulfan and Thiotepa followed by autologous stem cell rescue without the use of radiation therapy. Remarkably the patient remains without evidence of recurrence 5 years after completion of therapy. Additional studies are necessary to determine the role of HDC and stem cell rescue in patients with recurrent CPC.